1990
DOI: 10.1093/intimm/2.10.973
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the CD68 macrophagr/myeloid associated antigen

Abstract: The distribution of the pan-macrophage CD68 antigen, recognized by six different monoclonal antibodies, was examined in human blood, tissue, and cell lines using APAAP staining and Western blotting. All antibodies stained monocytes and macrophages, but labelling of neutrophils, basophils, and lymphocytes was seen with some of the reagents. In addition, the CD68 antibodies demonstrated a variety of staining patterns on some non-haemopoietic cells. The subtle differences between the reactions of the different an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 0 publications
8
131
0
1
Order By: Relevance
“…S3). In agreement with historic literature (31,32), these results thus indicate that CD68 is not a macrophage-specific marker in human BC.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S3). In agreement with historic literature (31,32), these results thus indicate that CD68 is not a macrophage-specific marker in human BC.…”
Section: Resultssupporting
confidence: 92%
“…Although used successfully in multiple studies to relate TAM infiltration with clinically relevant outcomes, our results indicate that CD68 alone cannot accurately evaluate macrophage presence in human breast tissue given that multiple stromal cells express it and that a subset of these are CSF1R-and CD45-negative. We observed that the nonleukocytic CD68 + cells were predominantly located within tumor stroma and, thus, based on this localization and morphology, we speculate that CSF1R − CD68 + cells likely reflect tumor-associated fibroblasts or monocyte-derived fibrocytes in agreement with other reports (31,32,(49)(50)(51)(52). Our findings do not invalidate CD68 as a clinically relevant marker and, importantly, CSF1-response gene signatures have been identified in breast adenocarcinomas that are predictive of recurrence risk and metastasis (53,54).…”
Section: Discussionsupporting
confidence: 90%
“…The genes selected for our study cover a broad spectrum of macrophage actions. CD68 is a transmembrane glycoprotein particularly highly expressed in human monocytes and tissue macrophages, participating in lectin/selectin-mediated cell adhesion and locomotion (32). EMR1 is also a transmembrane glycoprotein present in peripheral blood mononuclear cells and presumably involved in cell-cell interactions and activation of consecutive messenger cascades (6).…”
Section: Discussionmentioning
confidence: 99%
“…This lysosomal enzyme is usually expressed in granulocytes and macrophages/histiocytes, and indicates the cell's capability for phagocytic (digestive) activity. Therefore, we applied the commercially available monoclonal antibody against the epitope KP-1 of CD 68 (DAKO, Hamburg, Germany) [32,38].…”
Section: Immunohistochemical Staining Proceduresmentioning
confidence: 99%